Senyawa Alami sebagai Kandidat Obat Antikanker: Suatu Tinjauan Kimia Medisinal - Cheriel Dhiya Nazwa Alivia; Saeful Amin (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Cancer remains a major challenge in modern medicine due to drug resistance and the adverse effects of conventional therapies, making it one of the leading causes of death worldwide. Continuous scientific efforts aim to discover safer and more effective treatments. Owing to their structural diversity, strong bioactivity, and relatively low toxicity, natural compounds show great promise as sources of anticancer drug candidates. This article aims to explore the role of medicinal chemistry in investigating, modifying, and optimizing natural bioactive compounds to develop more effective, selective, and stable anticancer agents with improved bioavailability. A narrative review was conducted using scientific literature published between 2020 and 2025 from PubMed, ScienceDirect, Google Scholar, and ResearchGate. The findings indicate that eugenol, berberine, hesperidin, piperine, and quercetin exhibit anticancer activities through apoptosis induction, inhibition of proliferation, and antioxidant and anti-inflammatory mechanisms. Modern medicinal chemistry relies on understanding structure–activity relationships (SAR), chemical modification, and nanoparticle formulation to enhance biological performance. In addition, in silico techniques such as molecular docking and QSAR analysis are applied to study ligands and receptors and predict bioavailability improvements. The development of natural products as rational, effective, and safe anticancer drug candidates is strengthened by integrating experimental, computational, and pharmaceutical approaches.